2023
DOI: 10.1021/acs.jctc.3c00842
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Equilibrium and Nonequilibrium Approaches for Relative Binding Free Energy Predictions

Shunzhou Wan,
Agastya P. Bhati,
Peter V. Coveney

Abstract: Alchemical relative binding free energy calculations have recently found important applications in drug optimization. A series of congeneric compounds are generated from a preidentified lead compound, and their relative binding affinities to a protein are assessed in order to optimize candidate drugs. While methods based on equilibrium thermodynamics have been extensively studied, an approach based on nonequilibrium methods has recently been reported together with claims of its superiority. However, these clai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…In addition, the EQ and NEQ ABFE approaches yield similar binding free energy estimates for the compounds binding to BTK (Figure ). This result is consistent with published studies on more extensive protein–ligand test sets. ,, We find that error estimates (derived from the standard deviation of three independent repeats) tend to be slightly larger for the NEQ approach than for the EQ approach (Tables and ). The NEQ approach is traditionally more computationally efficient than the EQ approach but requires that several critical parameters be considered for reliable, accurate, and precise free energy estimates. , Overall, the agreement in predicted free energy estimates between the EQ and NEQ ABFE approaches provides an independent check of our results in the absence of comprehensive experimental data.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, the EQ and NEQ ABFE approaches yield similar binding free energy estimates for the compounds binding to BTK (Figure ). This result is consistent with published studies on more extensive protein–ligand test sets. ,, We find that error estimates (derived from the standard deviation of three independent repeats) tend to be slightly larger for the NEQ approach than for the EQ approach (Tables and ). The NEQ approach is traditionally more computationally efficient than the EQ approach but requires that several critical parameters be considered for reliable, accurate, and precise free energy estimates. , Overall, the agreement in predicted free energy estimates between the EQ and NEQ ABFE approaches provides an independent check of our results in the absence of comprehensive experimental data.…”
Section: Resultssupporting
confidence: 91%
“…The calculations were performed for both wildtype and mutant states of BTK. For details about the EQ and NEQ binding free energy approaches, including challenges and directions for future method development, see recent work by Baumann et al, Coveney and co-workers …”
Section: Methodsmentioning
confidence: 99%
“…In recent years, alchemical free-energy calculations have become established as essential tools to support drug discovery projects by helping to prioritize compounds for synthesis. The groundwork behind these methods dates back to pioneering theoretical work in the 20th century, followed by subsequent efficiency improvements relying on their combination with various enhanced-sampling algorithms (for examples, see refs ). While these methods perform well for series of congeneric ligands, , it is typically challenging to estimate relative binding free energies between molecules with different net charges, scaffolds, or binding modes. , In particular, transformations involving ligands with different charges face two main challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported non-Gaussian behavior for different QoIs in various applications. 3 8 In the context of MD simulations, we have reported on numerous occasions the observation of non-Gaussian distributions in binding free energies calculated from both equilibrium 9 14 and nonequilibrium 15 approaches. The observation of non-Gaussian distributions from simulations led to the investigation of exceptionally extensive experimental data the results of which we published recently in JCIM.…”
mentioning
confidence: 99%